Light‐microscopic examinations of sperm in several lineages of Carabidae (Insecta: Coleoptera): Implications for the evolution of sperm conjugation. Issue 3 (27th June 2020) - Sasakawa, Kôji
Abstract: Sperm show marked morphological diversity, but the processes and mechanisms driving this diversity have not been fully elucidated. The beetle family Carabidae represents a potential model system for studying sperm trait evolution. In this study, sperm traits (mainly conjugation and sperm conjugate gross morphology) of 42 species from nine subfamilies of Carabidae were examined using light microscopy. Except in Harpalinae, the type of conjugation was shared by all members of a particular subfamily: in Carabinae, Elaphrinae, Patrobinae and Brachinae, sperm conjugates were observed in which variable numbers of sperm clumped together; in Nebriinae, Cicindelinae and Trechinae, sperm were not organized as conjugates but were present individually; and in Broscinae, both individual sperm and sperm conjugates were observed. In the remaining subfamily, Harpalinae, sperm conjugates were formed in most species, but a loss of conjugation was observed in some species. Mapping the observed sperm traits onto within‐family molecular phylogenetic trees suggested that sperm conjugation was ancestral, with loss of conjugation evolving in several lineages. In sperm conjugates, a short spermatostyle (the axis of sperm conjugates) was the ancestral state, while a long spermatostyle evolved in subsequent lineages. In the long spermatostyle trait, the flexible type without a conspicuous 3D structure was ancestral, while the type with a conspicuous 3D structure, such as the spiral structure, evolved in derived lineages. Abstract : Sperm traits (mainly conjugation and sperm conjugate macromorphology) of 42 species from nine subfamilies of Carabidae were examined using light microscopy. Mapping the results of this and previous studies regarding sperm conjugates onto a within‐family molecular phylogenetic tree suggests evolutionary patterns of sperm conjugates in Carabidae.